THE POSSIBILITIES OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE CONTEXT OF A PANDEMIC - Moshkalov А.Қ.; Orazbekov Ж.Н.; Sabraev Қ.Ж.; Sharmukhanbet С.Р. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
To date, education has been recognized as one of the most important priorities of the long-term strategy «Kazakhstan-2050» and the improvement of the education system plays an important role in achieving this goal. Joining the world community and expanding the information space will increase the role of education in the formation of human resources as criteria for the level of socio-economic development of the country, and this is an important fact of the orientation of the education system to new requirements. The current state of society is characterized by information and technical saturation, due to the annual doubling of information, at which the rate of change of technologies and technologies exceeds the rate of change of generations. ICTs, being an important economic sector, have a direct impact on the productivity and efficiency of the economy, in particular on GDP growth and global poverty, and are important for achieving sustainable development goals. The COVID-19 pandemic has had a major impact on the development of ICT over the past two years. The article examines the importance of information and communication technologies in society and during the global pandemic, as well as the process of informatization of education, its main directions.